SYNERGISTIC EFFECT OF PLANT GROWTH PROMOTING RHIZOBACTERIA AND KINETIN ON MAIZE - S. Sabir; H. N. Asghar; S.U. R. Kashif; M. Y. Khan; M. J. Akhtar (Journal of Animal and Plant Sciences, 2013)
Plant growth promoting rhizobacteria (PGPR) colonize the plant roots and promote plant growth and yield by different mechanisms. A study was conducted in a series of jar and pot trials where effect of four different PGPR isolates alone and in combination with kinetin on maize (Zea mays L.) was evaluated under controlled and natural conditions. Results of jar trial indicated that PGPR isolates had positive interaction with the kinetin and significantly increased shoot and root length. However, the synergistic effect of PGPR isolates and kinetin was significantly better. Data of pot trial further confirmed the results of jar trial where combined use of bacterial strains with kinetin increased plant height (53%), shoot fresh weight (48%), root length (50%), shoot dry weight (133%), root fresh weight (37%) and root dry weight (70%) as compared to the sole application of kinetin. While interaction of PGPR with kinetin also improved the nitrogen, phosphorus and potassium contents in plant tissues as compared to control. Study revealed that plant growth promoting capabilities of PGPR could be improved if they are supplemented with exogenous kinetin.
Keywords: rhizobacteria; growth regulator; cytokinins